TRADISI LOKAL DALAM NYANYIAN RATAPAN “MUNABA” ETNIK WAROPEN, PAPUA: KAJIAN ANTROPOLOGI SASTRA - Belghita Sonei Risia Yenusi (Balai Bahasa Provinsi Papua, 2019)
This study focused on the local tradition in lamentation song “munaba” from Waropen ethnic, Papua. Munaba was selected due to its familiar and grounded in local communities in the area. Research approach is based on text and context. The approach focused on literary works and based on some aspects such as literature anthropology. The study used descriptive qualitative method which uncovered facts, phenomenon and variable. The study as well interpreted data related to given situation, the view points of society, conflicts, the difference between facts, and the influence of particular problem which was studied and investigated. The data was obtained from oral literature which was shared by the native speakers. In addition, the research also applied observation. Data source is munaba in Waropen language. The original data has been transliterated from a number of informants then it is translated into Indonesian language. Based on semiotic and hermeneutic theory, and also literature anthropology analysis, the study found some local tradition in munaba such as language, location, living system, social organization system, and tribal religion system of Waropen tribe in the lamentation song munaba.